Edukasi Pubertas Di SDN Karanggintung 1 Dan 2 Kelas V Dan VI Desa Karanggintung Tahun 2022 - Achamd Zakaria; Ruman; Teguh Wibowo (Pusat Riset dan Inovasi Nasional, 2022)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. The work program with the theme